A cubic diamond grain, a method of making the same and use in the production of a diamond sheet
By using a six-sided top press and MPCVD technology to prepare cubic diamond grains, the problems of low diamond wafer growth rate and high cost were solved, and the production of diamond wafers with high thermal conductivity and high strength was achieved, improving production efficiency and grain conversion rate.
Patent Information
- Application Number
- CN202511134222.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-14
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-08-14
AI Technical Summary
Existing diamond wafer growth methods suffer from problems such as low growth rate, limited area, high cost, and difficulty in controlling size and purity, especially in CVD and HPHT technologies.
Cubic diamond grains were prepared using a six-sided top press, combined with high-temperature and high-pressure synthesis of catalyst powder and graphite powder. By strictly controlling growth parameters and post-processing techniques, high-purity cubic diamond grains were prepared, and epitaxial growth was carried out using MPCVD technology, combined with a stacking machine to achieve single-layer close packing.
It improves the thermal conductivity and bending strength of diamond sheets, reduces production costs, meets the diverse needs of industrial tools and quantum devices, and achieves a diamond grain conversion rate of over 95.6%.
Smart Images

Figure CN120618350B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of diamond preparation, in particular to a cubic diamond grain, a preparation method thereof and application thereof in diamond sheet production. BACKGROUND
[0002] Diamonds have great application potential in high-end industries, electronic devices, optical elements and quantum technology due to their excellent physical and chemical properties (such as ultra-high hardness, extremely high thermal conductivity, wide bandgap semiconductor characteristics and excellent optical performance). However, its industrialized production application has been restricted by factors such as growth efficiency, crystal quality, size controllability and production cost for a long time, and it is urgent to break through the bottleneck through technological innovation.
[0003] Current diamond sheet growth methods mainly focus on optimization of chemical vapor deposition (CVD) and high temperature and high pressure (HPHT) technologies. The CVD method for growing diamond sheets has low growth rate, limited growth area and high cost. The size and purity of the diamond sheets grown by the HPHT method are limited, impurity defects are difficult to control, and the thermal conductivity is low. SUMMARY
[0004] Therefore, the purpose of the present application is to provide a cubic diamond grain, a preparation method thereof and application thereof in diamond sheet production, which solves the problems existing in the preparation of traditional diamond sheets by preparing a cubic diamond grain.
[0005] To solve the above technical problems, the present application adopts the following technical solutions:
[0006] A preparation method of a cubic diamond grain, comprising the following steps:
[0007] S1, preparing a catalyst powder
[0008] Iron powder, nickel powder, manganese powder and sulfur powder are weighed and ball milled under argon protection for 4-6 hours; the mass ratio of the iron powder, nickel powder and manganese powder is Fe: Ni: Mn = 14-16: 4-6: 1, and the sulfur powder accounts for 0.1-0.3wt% of the total mass of the metal powder; the ball-to-material ratio is 10:1 during ball milling, the rotation speed is 300 rpm / min, and the particle size is uniform (D50≈15μm);
[0009] S2, mixing
[0010] After the graphite powder is impurity-removed, the graphite powder and the catalyst powder are uniformly mixed in a mass ratio of 1:3.8-4.2 to obtain a graphite powder-catalyst mixture; the purity of the graphite powder is ≥99.999%, and the particle size is 30-80μm;
[0011] S3, preparing a cubic diamond by a six-face top press
[0012] The cubic diamond grains are synthesized by a cubic anvil press at high temperature and high pressure, and nitrogen N2 (purity ≥ 99.9999%) is added in the sealed microcavity at an amount of 50-100 mg / L. Nitrogen is used to precisely inhibit the growth of the (111) plane, and affects the final shape of the diamond grains;
[0013] In the present application, in order to adjust the size distribution of the diamond grains, boron is also added in the graphite powder, and the amount of boron (B) added is 5-20 mg / kg.
[0014] When the cubic diamond grains are prepared by the cubic anvil press, the specific steps are as follows:
[0015] First, the graphite powder-catalyst mixture is pressed into a cylinder with a diameter of 2.5-3 mm and a height of 4.5-5 mm, and the density is ≥ 3.5 g / cm³ to ensure tight contact. High-purity nitrogen in the sealed microcavity can prevent high-temperature oxidation.
[0016] Two tungsten-rhenium thermocouples need to be arranged in the center area and the edge area of the sealed microcavity to feedback and adjust the temperature in real time.
[0017] The pressure and time parameters in the center area of the sealed microcavity are set in stages:
[0018] ① In the pre-pressing stage, the pressure is set to 1.0-1.5 GPa, the temperature is room temperature (conventionally 25℃, following the working environment temperature), and the time is 2-3 min. The purpose is to compact the raw materials and eliminate voids.
[0019] ② In the pressure and temperature rising stage, the pressure is set to 5.5-6.0 GPa, the temperature in the center area is 1450-1550℃, and the time is 5-6 min. The purpose is to trigger nucleation and control density.
[0020] ③ In the steady growth stage, the pressure is 5.1-5.3 GPa, the temperature in the center area is 1400-1450℃, and the time is 8-10 min. The purpose is to limit the growth rate to about 0.025 mm³ / min.
[0021] ④ In the termination stage, the pressure is 5.0-5.2 GPa, the temperature in the center area is 1300-1350℃, and the time is 2-3 min. The purpose is to quickly terminate the growth and prevent the overgrowth of the (100) plane to obtain cubic diamond grains.
[0022] The edge area of the sealed microcavity is gradiently cooled to 1300-1400℃.
[0023] S4, after the cubic diamond grain preparation is first carried out acid washing purification treatment: dilute nitric acid (10% mass fraction HNO3, 40 DEG C) ultrasonic treatment 1 hour, to dissolve the catalyst;With hydrofluoric acid (5% mass fraction HF) immersion 20 minutes, remove the pyrophyllite residue;Washing purification: deionized water (conductivity <1 muS / cm) ultrasonic cleaning 30 minutes, remove the pickling residue;Ethanol immersion 30 min after vacuum drying (60 DEG C, 0.1 Pa, 2 hours).
[0024] After acid washing purification, the laser screening instrument is used, and the cubic diamond grain with a particle size of D50=50+2 mu m (D90 / D10<1.3) is screened out, and finally the surface of the cubic diamond grain is polished to a roughness Ra<10 nm.
[0025] The polished cubic diamond grain is used to prepare a diamond sheet, and the preparation method comprises the following steps:
[0026] S1, preparation of single crystal diamond substrate
[0027] 1, cubic diamond grain activation
[0028] The cubic diamond grain is activated by plasma cleaning machine by introducing O2, the power is 90W~100W, the time is 5min~8min, the gas pressure is 40pa~55Pa, and the O2 flow is 20~50 sccm;The activated cubic diamond grain is put into a 1% mass fraction KH-560 ethanol solution (silane coupling agent) and immersed for 10s~15s, and then put into a vacuum drying box and treated at 80 DEG C for 2 hours;In this step, the diamond grain activation is through plasma activation and silane coupling agent (KH-560) modification to improve the surface chemical activity, dispersibility and bonding performance of the diamond. Plasma activation is used to remove the diamond surface pollutants (such as adsorbed hydrocarbons, oxides), introduce oxygen-containing polar groups (—OH, —C=O, —COOH), and enhance the surface hydrophilicity;Silane coupling agent is used to combine with —OH on the surface of diamond grain through silicon-oxygen bond (—Si—O—), introduce epoxy group (—CH(O)CH2), and improve the interface bonding force of resin / metal matrix.
[0029] 2, closely arranged diamond grains
[0030] Micro-hole array preparation of photoetching template is carried out using AZ 5214 photoresist, and the photoetching template is attached to the surface of the ceramic substrate and fixed by vacuum adsorption; diamond grains are dispersed in a 5% (mass percentage) isopropanol or ethanol solution (containing 5% (mass percentage) surfactant Triton X-100 to improve wettability), the surface tension is reduced, and the grains are prevented from agglomeration, and then the diamond grains are drop-casted onto the surface of the photoetching template; the centrifuge is used for centrifugal filling (800 rpm / min, 10 minutes) to force the diamond grains to be embedded in the micro-holes of the photoetching template; then the photoresist is dissolved (5-minute acetone immersion), and a single-layer closely arranged diamond substrate is obtained. In the present application, the cubic diamond grains with uniform shape are more easily and stably embedded in the micro-holes when embedded in the photoetching template, compared with other shapes of diamond grains, for example, compared with regular hexahedral diamond grains, the cubic diamond grains have sharp corners, have a large side wall contact area after being embedded in the micro-holes, are not easy to rotate or displace, and avoid forming triangular pores when hexahedral stacking is formed; compared with cuboid diamond grains, the randomness of the long axis direction does not need to be considered, all the grains are tiled in the same orientation (100 plane upward), and the arrangement is more compact.
[0031] 3、Arrangement and fixation process
[0032] After the UV curing glue (epoxy resin) is pre-coated, the UV light (365 nm) is irradiated for 5 seconds for curing. The obtained single-crystal diamond substrate has a side length size of 2 mm to 5 mm.
[0033] S2, Microwave plasma chemical vapor deposition preparation of diamond sheet
[0034] 1、Single-crystal diamond substrate pretreatment
[0035] The single-crystal diamond substrate is placed on a tray (molybdenum tray or silicon tray), and the tray is fixed by a graphite clamp (to avoid metal contamination). First, hydrogen plasma etching is performed: hydrogen gas (hydrogen purity 99.999%) is introduced into the equipment cavity of the microwave plasma chemical vapor deposition system (MPCVD), the power is 1500 W, the pressure is 50 Torr, and the etching is performed for 120 minutes to activate the surface of the single-crystal diamond substrate and form hydrogen-terminated C-H bonds; then H2 (200 sccm) is continuously introduced, the pressure is 30 Torr, the microwave power is 1000 W, the temperature is raised to 800℃, and the heat field is preheated for 10 minutes to stabilize the thermal field and avoid stress cracking of the epitaxial layer caused by temperature gradient;
[0036] 2、Epitaxial growth stage
[0037] Proportionally introduce CH4 / H2 / N2, wherein the volume ratio of CH4:H2 is 2:98~4:96, and N2=45mg / L~50 mg / L (inhibit graphite phase). Then gradually increase the microwave power to 3000 W, adjust the pressure to 100 Torr, and observe the stable coverage of the plasma ball on the substrate; the probe of the emission spectrometer is aligned with the plasma ball, the light intensity signals of 656 nm (Halpha) and 516 nm (C2) are collected in real time, the Halpha (656 nm) and C2 (516 nm) intensity ratio is monitored in real time, and it is ensured that Halpha / C2>3 (inhibit graphite phase), the process can control the value of Halpha / C2 by adjusting the CH4 / H2 ratio, and the substrate temperature is ensured to be stable at 900±10 DEG C through infrared temperature measurement during the process.
[0038] 3. Termination and cooling
[0039] Stop the input of CH4, and maintain pure H2 for 10 minutes to etch the amorphous carbon on the surface; stepwise cooling: the microwave power is reduced to 0 at a rate of 500 W / 10 min, and the substrate is naturally cooled to below 200 DEG C and taken out;
[0040] 4. Post-processing
[0041] Hydrogen plasma etching: hydrogen plasma etching at 800 DEG C for 0.5~1h to repair the surface defects;
[0042] Mechanical polishing: diamond abrasive paste (particle size 0.1 mu m) is used to polish the surface of the diamond sheet to a roughness Ra<5 nm.
[0043] Compared with the prior art, the present application has the beneficial effects that:
[0044] 1. Through process improvement, the growth surface of the grown diamond crystal grain is controlled, the conversion rate of the cubic diamond crystal grain is above 95.6%, and more cubic diamond crystal grains can be obtained;
[0045] 2. The single-layer cubic diamond is closely arranged by combining the arrangement machine, the density of the diamond crystal grain is improved, the gap between the diamond crystal grains is reduced compared with the prior art, and the thermal conductivity of the diamond sheet is greatly improved;
[0046] 3. Through the combination and complementary advantages of HPHT+arrangement machine+MPCVD, the diamond sheet has both strength advantage and purity advantage, and the thermal conductivity, mechanical property and optical property are greatly improved compared with the traditional preparation method; the present application utilizes HPHT to produce the substrate on a large scale, greatly reduces the time consumption and energy consumption of the MPCVD process; in addition, the diamond sheet of the present application has the customizability of structure, doping and function, and meets the diversified needs from industrial tools to quantum devices. BRIEF DESCRIPTION OF DRAWINGS
[0047] Figure 1The photograph of the cubic diamond grains prepared in Example 1 of the present application under 50 times magnification of a hand-held microscope;
[0048] Figure 2 The photograph of the diamond sheet prepared in Example 5 of the present application;
[0049] Figure 3 The photograph of the cubic diamond grains prepared in Example 2 of the present application under 30 times magnification of a hand-held microscope;
[0050] Figure 4 The photograph of the cubic diamond grains prepared in Example 3 of the present application under 30 times magnification of a hand-held microscope;
[0051] Figure 5 The model diagram of the single crystal diamond substrate in Example 4 of the present application;
[0052] Figure 6 The photograph of the single crystal diamond substrate in Example 4 of the present application under 50 times magnification of a hand-held microscope;
[0053] Figure 7 The photograph of the diamond grains prepared in Comparative Example 1 of the present application under 30 times magnification of a hand-held microscope;
[0054] Figure 8 The photograph of the diamond grains prepared in Comparative Example 2 of the present application under 30 times magnification of a hand-held microscope;
[0055] Figure 9 The photograph of the cubic diamond grains prepared in Comparative Example 3 of the present application under 30 times magnification of a hand-held microscope. DETAILED DESCRIPTION
[0056] In order to make the skilled in the art more clearly and intuitively understand the present application, the present application will be further described below in combination with the drawings.
[0057] Example 1
[0058] Preparation of cubic diamond grains by HPHT method
[0059] S1, preparation of catalyst powder:
[0060] The iron powder, nickel powder, manganese powder, sulfur powder and boron powder were weighed and ball milled together under argon protection for 5 hours, the ball-to-material ratio was 10:1, the rotation speed was 300 rpm / min, and the particle size was uniform (D50≈15 μm); wherein, Fe:Ni:Mn=14:5:1, the sulfur powder accounted for 0.1wt% of the total weight of the metal powder, and the addition amount of B was 10 mg / kg.
[0061] S2, after the graphite powder (purity 99.99%, particle size 50 μm) is impurity-removed, the catalyst is uniformly mixed with the graphite powder at a mass ratio of 1:4 to obtain a graphite powder-catalyst mixture; in this embodiment, the impurity-removal treatment is vacuum degassing (10 -4 Pa, 300℃, 30min) to adsorb impurities;
[0062] S3, cubic diamond prepared by a cubic press
[0063] The cubic diamond is prepared by a cubic press under high temperature and high pressure, and the nitrogen N2 (purity ≥ 99.9999%) is added in the sealed microcavity at an amount of 75 mg / L. When the cubic diamond is prepared by the cubic press, the specific steps are as follows:
[0064] The graphite powder-catalyst mixture is pressed into a cylinder with a diameter of Φ2.8 mm and a length of 4.8 mm, and the density is ≥ 3.5 g / cm³ to ensure close contact. In addition, nitrogen is pre-charged into the sealed microcavity to prevent high-temperature oxidation;
[0065] ① The pre-pressing stage: the pressure is set to 1.2 GPa, the temperature is room temperature, and the time is 2 min, so as to further compact the raw material and eliminate the voids;
[0066] ② The pressure and temperature increasing stage: the pressure is set to 5.5 GPa, the center region temperature is 1450℃, and the time is 6 min, so as to trigger nucleation and control the density;
[0067] ③ The steady growth stage: the pressure is 5.1 GPa, the center region temperature is 1420℃, and the time is 10 min, so as to limit the growth rate to 0.025 mm³ / min;
[0068] ④ The termination stage: the pressure is 5.2 GPa, the center region temperature is 1350℃, and the time is 2 min, so as to quickly terminate the growth and prevent overgrowth.
[0069] Edge region: (W-Re) thermocouple feedback combined with water-cooling power regulation, gradient cooling to 1300℃, to control the growth rate (limit the growth rate); the edge region is the peripheral position of the reaction chamber (about 10~20 mm away from the chamber wall), the target temperature is 1300℃ (which is the carbon atom diffusion driving zone), and if it exceeds this target temperature, it will cause carbon diffusion to be blocked and stress accumulation. S4, post-processing: dilute nitric acid (10% mass fraction HNO3, 40℃) ultrasonic treatment for 1 hour; soak in hydrofluoric acid (5% mass fraction HF) for 20 minutes, and then ultrasonic clean with deionized water (conductivity <1 μS / cm) for 30 minutes; then soak in ethanol for 30 min and vacuum dry (60℃, 0.1 Pa, 2 hours). The particles with a particle size of about D50=50±2 μm, D90 / D10<1.3, are sorted by a laser sizer. According to the mass of the obtained cubic diamond grains / total carbon mass of the added carbon source, the conversion rate of the cubic diamond grains of Example 1 is above 96.0%.
[0070] The screening structure of the diamond grains of Example 1 is shown in Table 1.
[0071] Table 1 Screening results of diamond grains in Example 1
[0072]
[0073] Finally, the diamond surface is polished to a roughness Ra<10 nm, and cubic morphology diamond grains are obtained, as shown in Figure 1 , the dislocation density is <10 5 cm -2 , and the thermal conductivity is about 1200 W / m·K.
[0074] Example 2
[0075] Preparation of cubic diamond particles by HPHT method
[0076] S1, Preparation of catalyst:
[0077] Iron powder, nickel powder, manganese powder, sulfur powder, and boron powder are weighed and ball milled together under argon protection for 4 hours, with a ball-to-material ratio of 10:1 and a rotation speed of 300 rpm, to ensure uniform particle size (D50≈15 μm); wherein Fe:Ni:Mn=15:4:1, the sulfur powder accounts for 0.3wt% of the total weight of the metal powder, and the addition amount of B is 20 mg / kg.
[0078] S2, After impurity removal, the graphite powder (purity 99.99%, particle size 80 μm) is uniformly mixed with the catalyst at a mass ratio of 1:4.2; in this embodiment, the impurity removal treatment is vacuum degassing (10 -4 Pa, 300℃, 30min) to adsorb impurities;
[0079] S3, Cubic diamond prepared by cubic anvil press
[0080] Cubic diamond was synthesized by high temperature and high pressure in cubic anvil press, and the nitrogen N2 (purity ≥ 99.9999%) was added at 100 mg / L. When the cubic diamond was prepared by the cubic anvil press, the specific steps were as follows:
[0081] The graphite powder-catalyst mixture was pressed into a Φ2.5*4.5 mm cylinder with a density of ≥3.5 g / cm³ to ensure close contact, and nitrogen was additionally pre-charged to the sealed microcavity to prevent high-temperature oxidation;
[0082] ① Pre-pressing stage: the pressure was set to 1.5 GPa, the temperature was room temperature, and the time was 2.5 min, to further compact the raw materials and eliminate voids;
[0083] ② Pressure and temperature rising stage: the pressure was set to 5.7 GPa, the center region temperature was 1500℃, and the time was 5.5 min, to trigger nucleation and control density;
[0084] ③ Steady growth stage: the pressure was 5.2 GPa, the center region temperature was 1400℃, and the time was 8 min, to limit the growth rate to 0.025 mm³ / min;
[0085] ④ Termination stage, the pressure was 5.0 GPa, the center region temperature was 1300℃, and the time was 3 min, to quickly terminate growth and prevent overgrowth.
[0086] Edge region: (W-Re) thermocouple feedback combined with water-cooled power regulation, gradient cooling to 1350℃, to control the growth rate (limit the growth rate); the edge region is the peripheral position of the reaction cavity (about 10~20 mm away from the cavity wall), and the target temperature is 1350℃ (which is the carbon atom diffusion driving zone), and if the target temperature is exceeded, carbon diffusion will be blocked and stress will accumulate.
[0087] S4, Post-processing: ultrasonic treatment with dilute nitric acid (10% HNO3, 40℃) for 1 hour; soak in hydrofluoric acid (5% HF) for 20 minutes, and then ultrasonic cleaning with deionized water (conductivity <1 μS / cm) for 30 minutes; then soak in ethanol for 30 min and vacuum dry (60℃, 0.1 Pa, 2 hours). The crystal grains with a particle size of about D50=50±2 μm, D90 / D10<1.3, were sorted by a laser sizer. According to the mass of the obtained cubic diamond crystal grains / the total carbon mass of the added carbon source, the conversion rate of the cubic diamond crystal grains of Example 2 was above 95.8%.
[0088] Finally, the diamond surface was polished to a roughness Ra<10 nm, and the cubic diamond crystal grains were obtained, as shown in Figure 3The dislocation density is <10 5 cm -2 The thermal conductivity is about 1000 W / m·K.
[0089] Example 3
[0090] HPHT method for preparing cubic diamond particles
[0091] S1, preparation of catalyst:
[0092] The iron powder, nickel powder, manganese powder, sulfur powder and boron powder were weighed and ball milled together under argon protection for 6 hours. The ball-to-material ratio was 10:1 and the rotation speed was 300 rpm to ensure uniform particle size (D50≈15μm). Among them, Fe:Ni:Mn=16:6:1, the sulfur powder accounted for 0.2wt% of the total weight of the metal powder, and the addition amount of B was 5mg / kg.
[0093] S2, after impurity removal, the graphite powder (purity 99.99%, particle size 30μm) was uniformly mixed with the catalyst at a mass ratio of 1:3.8. In this embodiment, the impurity removal treatment was vacuum degassing (10 -4 Pa, 300℃, 30min) to adsorb impurities;
[0094] S3, cubic diamond prepared by a cubic anvil press
[0095] The cubic anvil press was used to synthesize cubic diamond at high temperature and high pressure, and the nitrogen N2 (purity ≥99.9999%) addition amount was 50mg / L. When the cubic anvil press was used to prepare cubic diamond, the specific steps were as follows:
[0096] The graphite powder-catalyst mixture was pressed into a Φ3.0×5.0mm cylinder with a density ≥3.5 g / cm³ to ensure tight contact. Nitrogen was also pre-charged into the sealed microcavity to prevent high-temperature oxidation.
[0097] ① Pre-pressing stage: the pressure was set to 1.0GPa, the temperature was room temperature, and the time was 3min to further compact the raw materials and eliminate voids.
[0098] ② Pressure and temperature rising stage: the pressure was set to 6.0GPa, the center region temperature was 1550℃, and the time was 5min to trigger nucleation and control density.
[0099] ③ Steady growth stage: the pressure was 5.3GPa, the center region temperature was 1450℃, and the time was 9min to limit the growth rate to 0.025mm³ / min.
[0100] ④ Termination stage, the pressure was 5.1GPa, the center region temperature was 1325℃, and the time was 2.5min to quickly terminate the growth and prevent overgrowth.
[0101] Edge region: (W-Re) thermocouple feedback combined with water-cooling power regulation, gradient cooling to 1400℃, to control the growth rate (limit the growth rate); the edge region is the peripheral position of the reaction chamber (about 10~20 mm away from the chamber wall), the target temperature is 1400℃ (which is the carbon atom diffusion driving zone), and if it exceeds this target temperature, it will cause carbon diffusion to be blocked and stress accumulation.
[0102] S4, post-processing: dilute nitric acid (10% HNO3, 40℃) ultrasonic treatment for 1 hour; soak in hydrofluoric acid (5% HF) for 20 minutes, and then ultrasonic clean with deionized water (conductivity <1 μS / cm) for 30 minutes; then soak in ethanol for 30 min and vacuum dry (60℃, 0.1 Pa, 2 hours). The particles with a particle size of about D50=50±2 μm, D90 / D10<1.3, are sorted by a laser sizer. According to the mass of the obtained cubic diamond grains / total carbon mass of the added carbon source, the conversion rate of the cubic diamond grains of Example 1 is above 95.6%.
[0103] Finally, the diamond surface is polished to a roughness Ra<10 nm, and a cubic morphology diamond grain is obtained, as shown in FIG. 1C. Figure 4 The dislocation density is <10 5 cm -2 , and the thermal conductivity is about 1100 W / m·K.
[0104] Example 4
[0105] A large-size (5 mm x 5 mm) single crystal diamond substrate is prepared using the cubic diamond grains prepared in Example 1, and a model diagram thereof is shown in FIG. 2A. Figure 5
[0106] The preparation method of the single crystal diamond substrate includes the following steps:
[0107] 1. Diamond grain activation: use a plasma cleaning machine to pass O2 to plasma activate the diamond grains, power 100 W, time 5 min, gas pressure 50 Pa, O2 flow rate 40 sccm (the above parameters can be adjusted within the following ranges: 90~100 W, time 5~8 min, gas pressure 40~55 Pa, O2 flow rate 20~50 sccm), and then put the activated diamond grains into a 1% KH-560 ethanol solution (silane coupling agent) for 10 seconds~15 seconds, and then put them into a vacuum drying oven for 2 hours at 80℃.
[0108] 2. Tight arrangement of diamond grains
[0109] Micro-hole array preparation of photoetching template using AZ 5214 photoresist, and make it fit on the surface of ceramic substrate, vacuum adsorption fixation; Disperse diamond grains in ethanol solution (containing 5% mass percentage of surfactant TritonX-100 to improve wettability), then drop coating diamond grains to the template surface; Fill by centrifuge (800 rpm / min, 10 minutes), force diamond grains to embed into the micro-holes of the photoetching template, coverage > 95%, inter-particle gap < 1 μm; Then dissolve the photoresist (acetone soaking for 5 minutes), and obtain a single layer of closely arranged diamond substrate;
[0110] 3、After arrangement and fixation process
[0111] UV curing glue (epoxy resin) pre-coating: after pre-coating DELO KATIOBOND 4592 (Germany DELO), irradiate with ultraviolet light (365 nm) for 5 seconds to solidify, and obtain a partial photo of the single crystal diamond substrate as shown in Figure 6 , which shows the neat and close arrangement of cubic diamond grains.
[0112] Example 5
[0113] Microwave plasma chemical vapor deposition of diamond sheet
[0114] 1、Single crystal diamond substrate pretreatment
[0115] Place the single crystal diamond substrate prepared in Example 4 on a molybdenum tray or a silicon tray, and fix it with a graphite clamp (to avoid metal contamination). First, perform hydrogen plasma etching: introduce hydrogen gas (hydrogen purity 99.999%) into the equipment cavity of the microwave plasma chemical vapor deposition system (MPCVD), power 1500 W, pressure 50 Torr, etching for 120 minutes, to activate the surface of the single crystal diamond substrate and form C-H bonds on the hydrogen-terminated surface.
[0116] Then continue to introduce H2 (200 sccm), pressure 30 Torr, microwave power 1000 W, heat to 800℃, preheat for 10 minutes to stabilize the thermal field, and avoid stress cracking of the epitaxial layer caused by temperature gradient;
[0117] 2、Epitaxial growth phase
[0118] Proportionally introduce CH4 / H2 / N2, wherein the volume ratio of CH4:H2 is 2:98~4:96, N2=45 mg / L~50 mg / L (inhibit graphite phase). Then gradually increase the microwave power to 3000 W, adjust the pressure to 100 Torr, and observe the stable coverage of the plasma ball on the substrate; the probe of the emission spectrometer is aligned with the plasma ball, and the light intensity signals of 656 nm (Hα) and 516 nm (C2) are collected in real time, the Hα (656 nm) and C2 (516 nm) intensity ratio is monitored in real time, and Hα / C2>3 (inhibit graphite phase) is ensured. During the monitoring process, the content of CH4 and H2 can be adjusted to control Hα / C2.
[0119] Substrate temperature: 900℃±10℃, growth time: 40 hours. Epitaxial layer thickness: 0.1 mm, total thickness 0.3 mm (0.2 mm of particle base + 0.1 mm of epitaxial layer).
[0120] 3. Termination and cooling
[0121] Stop inputting CH4, maintain pure H2 for 10 minutes, etch the surface amorphous carbon; step-down cooling: reduce the microwave power to 0 at a rate of 500 W / 10 min, and naturally cool to below 200℃ to take out the substrate;
[0122] 4. Post-processing
[0123] Hydrogen plasma etching: hydrogen plasma etching at 800℃ for 0.5~1h to repair surface defects;
[0124] Mechanical polishing: diamond abrasive paste (particle size 0.1μm) is used to polish the surface of the diamond sheet to a roughness Ra<5nm.
[0125] 5. Performance results:
[0126] The actual diamond sheet obtained is as shown in Figure 2 The thermal conductivity is above 1550 W / m·K (isotropic), the local hot spot heat dissipation efficiency is improved by 30%, the bending strength is above 800MPa, and the cost comparison: the expensive single crystal substrate is replaced by HPHT prepared diamond particles, and compared in terms of production efficiency, the cost of this method is reduced by 60% compared with traditional MPCVD single crystal substrate.
[0127] Example 6
[0128] The cubic diamond grains prepared in Example 2 are used to prepare single crystal diamond substrates by the method of Example 4, and diamond sheets are prepared by the method of Example 5, and the thermal conductivity of the obtained diamond sheet is 1500 W / m·K, and the bending strength is above 800MPa.
[0129] Example 7
[0130] Similarly, the cubic diamond grains prepared in Example 3 were used to prepare a single crystal diamond substrate by the method of Example 4, and a diamond sheet was prepared by the method of Example 5, and the thermal conductivity of the obtained diamond sheet was 1510 W / m·K, and the bending strength reached more than 800 MPa.
[0131] Comparative Example 1
[0132] The difference between this comparative example and Example 1 is the amount of nitrogen added, specifically, the N2 addition amount is 25 mg / L when preparing diamond grains in a cubic press. Since the addition of nitrogen mainly acts to inhibit the graphite phase and inhibit the growth of the 111 plane, the addition amount of nitrogen in this comparative example is insufficient to inhibit the growth of the 111 plane, and therefore, the particles with a particle size of about 50±2 μm are finally separated by a vibrating screen, and it is found that the obtained diamond grains have obvious defects. The morphology of the diamond grains is shown in Figure 7 5 cm -2 , and the thermal conductivity is about 1000 W / m·K.
[0133] The cubic diamond grains prepared in Comparative Example 1 were used to prepare a large-size single crystal diamond substrate by the method of Example 4, and then a diamond sheet was prepared by the method of Example 5, and the performance of the prepared diamond sheet was detected: thermal conductivity: 1200 W / m·K (isotropic), local hot spot heat dissipation efficiency is increased by 10%. Bending strength: about 750 MPa.
[0134] Therefore, by reducing the amount of nitrogen in Comparative Example 1, the diamond grains cannot generate cubes, and therefore, the diamond grains cannot be closely arranged during the preparation of the diamond substrate, thereby ultimately affecting the performance of the diamond sheet.
[0135] Comparative Example 2
[0136] The difference between this comparative example and Example 1 is the pressure, specifically, the pressure in the steady-state growth stage and the termination stage is increased when preparing cubic diamond in a cubic press.
[0137] The pre-pressing stage: the pressure is set to 1.2 GPa, the temperature is room temperature, and the time is 2 min, to further compact the raw material and eliminate voids; the pressure increasing and temperature increasing stage: the pressure is set to 5.5 GPa, the center region temperature is 1450℃, and the time is 6 min, to trigger nucleation and control density;
[0138] The steady-state growth stage: the pressure is 6.0 GPa, the center region temperature is 1420℃, and the time is 10 min, to limit the growth rate to 0.025 mm³ / min;
[0139] The termination stage is 6.0 GPa, the center region temperature is 1350℃, and the time is 2 min, so as to quickly terminate the growth and prevent overgrowth.
[0140] In the four stages of diamond growth, the pressure in the steady growth stage is crucial, mainly reflected in the crystal defects caused by high pressure and the inactivation of the catalytic interface. Finally, the diamond particles with a size of about 50±2 μm are sorted by a laser screening instrument, and it is found that the obtained diamond grains are non-normal diamond grains, and the morphology of the diamond grains is as shown in Figure 8 The thermal conductivity thereof is 680 W / m·K, and the dislocation density is <10 7 cm -2 , D90 / D10 is about 1.5, and the particle size distribution is relatively scattered.
[0141] The cubic diamond grains prepared in the comparative example 2 are used to prepare large-size single-crystal diamond substrates by the method of example 4, and then the diamond sheets are prepared by the method of example 5. The performance detection of the prepared diamond sheets shows that the thermal conductivity is 800 W / m·K (isotropic), and the bending strength is about 600 MPa.
[0142] Therefore, the comparative example 2 increases the pressure in the steady growth stage and the termination stage, so that the diamond grains cannot generate cubes, and thus the diamond grains cannot be closely arranged in the preparation of the diamond substrate, thereby finally affecting the performance of the diamond sheet.
[0143] Comparative example 3
[0144] The difference between the present comparative example and example 1 is that no B element is added, specifically, no B element is added in the preparation of the catalyst. Since the role of the B element is to adjust the size distribution of the diamond grains, finally, the particles with a size of about 50±2 μm are sorted by a laser screening instrument, and the obtained diamond grains are rectangular diamond grains, as shown in Figure 9 It is found that the dislocation density is <10 6 cm -2 , D90 / D10 is <1.5, the particle size distribution is relatively scattered, and the thermal conductivity is about 850 W / m·K.
[0145] The cubic diamond grains prepared in the comparative example 3 are used to prepare large-size single-crystal diamond substrates by the method of example 4, and then the diamond sheets are prepared by the method of example 5. The performance detection of the prepared diamond sheets shows that the thermal conductivity is 1100 W / m·K (isotropic), and the bending strength is 650 MPa.
[0146] Comparative example 4
[0147] The difference between the present comparative example and example 1 is that 30 mg / L of element B is added, specifically, an excess of element B is added during the preparation of the catalyst. Since the role of element B is to adjust the size distribution of diamond grains, it is found that the dislocation density is <3×10 5 cm -2 , D90 / D10 <1.9, the particle size distribution is relatively scattered, and the thermal conductivity is about 600 W / m·K.
[0148] The cubic diamond grains prepared in Comparative Example 4 are used to prepare large-size single-crystal diamond substrates by the method of Example 4, and then the diamond sheets are prepared by the method of Example 5. The performance of the prepared diamond sheets is detected: thermal conductivity: 800 W / m·K (isotropic), bending strength: 650 MPa.
[0149] From the results of the examples and comparative examples, it can be seen that, by strictly controlling the amount of nitrogen added in the cubic anvil press (excess nitrogen will seriously affect the quality of diamond, and will also cause safety risks and process control problems of the equipment) and the amount of boron element added, and strictly controlling the forming pressure, the cubic diamond grains can be precisely controlled to grow in 100 faces, which lays an important foundation for the subsequent preparation of diamond substrate with close-packed diamond grains. The finally prepared diamond sheet has excellent thermal conductivity and bending strength, and the thermal conductivity can reach more than 1500 W / m·K, and the bending strength can reach more than 800 MPa. In the present application, the shape of the diamond grains is very important, because the triangular pores formed by the stacking of regular hexahedral diamond grains affect the thermal conductivity, and the long cuboid diamond grains need to consider the randomness of the long axis direction, which affects the tightness of the arrangement. The cubic diamond grains of the present application have sharp corners and edges, and after embedding into the micropores, the side wall contact area is large, and it is not easy to rotate or displace, which has important advantages. In addition, in the preparation method of the cubic diamond grains in the present application, the conversion rate of the cubic diamond grains can be ensured to be more than 95.6%, more cubic diamond grains can be obtained, and the preparation efficiency is improved.
[0150] The above description of the examples is for the purpose of enabling and applying the present application to those of ordinary skill in the art. Those skilled in the art can easily make various modifications to these examples, and apply the general principles described herein to other examples without creative labor. Therefore, the present application is not limited to the examples herein, and improvements and modifications of the present application made by those skilled in the art based on the disclosure of the present application should be within the scope of protection of the present application.
Claims
1. A method for preparing cubic diamond grains, characterized in that, Includes the following steps: S1. Preparation of catalyst powder Iron powder, nickel powder, manganese powder, boron powder, and sulfur powder are weighed and ball-milled together under argon protection for 4-6 hours until the particle size is uniform; wherein, the mass ratio of iron powder, nickel powder, and manganese powder is iron powder: nickel powder: manganese powder = 14-16: 4-6: 1, the sulfur powder accounts for 0.1%-0.3% of the total mass of the metal powder, and the amount of boron powder added is 5-20 mg / kg; S2, Mixing After removing impurities from the graphite powder, it is uniformly mixed with the catalyst powder at a mass ratio of 1:3.8~4.2 to obtain a graphite powder-catalyst mixture. The particle size of the graphite powder is 30~80μm. S3, Preparation of cubic diamond grains using a six-sided top press First, the graphite powder-catalyst mixture is pressed into a cylinder with a density ≥3.5 g / cm³, and high-purity nitrogen is pre-filled into the sealed microcavity of the six-sided top press. The amount of high-purity nitrogen added is 50~100 mg / L. Pressure and time parameters are set in stages in the central region of the sealed microcavity: ① During the pre-compression stage, the pressure is set to 1.0 GPa~1.5 GPa, the temperature is room temperature, and the time is 2~3 min; ② During the pressure and temperature increase stage, the pressure is set to 5.5 GPa~6.0 GPa, the temperature of the central area of the sealed microcavity is 1450℃~1550℃, and the time is 5min~6min; ③ During the steady-state growth stage, the pressure is 5.1 GPa~5.3 GPa, the temperature in the central region of the sealed microcavity is 1400℃~1450℃, and the time is 8min~10min; ④ In the final stage, the pressure is 5.0 GPa to 5.2 GPa, the temperature in the central region of the sealed microcavity is 1330℃ to 1360℃, and the time is 2 to 3 minutes, thus obtaining cubic diamond grains.
2. The method for preparing cubic diamond grains as described in claim 1, characterized in that, The prepared cubic diamond grains were purified by acid washing and sieved to obtain cubic diamond grains with a particle size of D50=50±2μm. Finally, the surface of the diamond grains was polished to a roughness Ra<10nm.
3. The method for preparing cubic diamond grains as described in claim 2, characterized in that, The acid washing and purification process includes the following steps: first, ultrasonic treatment with 10% nitric acid, then soaking in 5% hydrofluoric acid, followed by ultrasonic cleaning with deionized water; finally, soaking in ethanol and vacuum drying.
4. The cubic diamond grains prepared by the preparation method according to any one of claims 1 to 3, wherein the thermal conductivity of the cubic diamond grains is above 1000 W / m·K.
5. The method for preparing a single-crystal diamond substrate using the cubic diamond grains described in claim 4, characterized in that, Includes the following steps: Activation of cubic diamond grains: The diamond grains are activated by plasma cleaning with oxygen. After activation, the diamond grains are impregnated with silane coupling agent and then dried in a vacuum drying oven. Densely arranged diamond grains: A photolithography template with a micropore array is attached to the substrate surface and fixed by vacuum adsorption; diamond grains are dispersed in an isopropanol or ethanol solution, and then the diamond grains are drop-coated onto the surface of the photolithography template; centrifugation is used to fill the diamond grains into the micropores of the photolithography template; After dissolving the photoresist, a single layer of closely packed diamond substrate can be obtained; After pre-coating with UV-curable adhesive, it is cured by irradiation with 365 nm ultraviolet light.
6. The single-crystal diamond substrate prepared by the method described in claim 5 has a side length of 2~5mm.
7. The method for preparing diamond sheets using the single-crystal diamond substrate as described in claim 6, characterized in that, Includes the following steps: Place the single-crystal diamond substrate on the tray and fix the tray with a clamp; first perform hydrogen plasma etching: introduce high-purity hydrogen into the equipment cavity of the microwave plasma chemical vapor deposition system, power 1500 W, pressure 50 Torr, and etch for 120 minutes; then continue to introduce hydrogen, pressure 30 Torr, microwave power 1000 W, heat up to 800℃, and preheat for 10 minutes. CH4 / H2 / N2 was introduced in a specific ratio, with a CH4:H2 volume ratio of 2:98 to 4:96 and an N2 content of 45 mg / L to 50 mg / L. The microwave power was then increased to 3000 W and the pressure adjusted to 100 Torr to induce a plasma sphere to cover the substrate. The probe of an emission spectrometer was aligned with the plasma sphere to collect light intensity signals at 656 nm and 516 nm in real time, monitoring the Hα to C2 intensity ratio to ensure Hα / C2 > 3. The substrate temperature was stabilized at 900 ± 10 °C. Then stop the CH4 input and maintain the pure hydrogen input for 10-15 minutes; finally, reduce the microwave power to 0 at a rate of 500W / 10min and allow it to cool naturally to below 200℃ to obtain the diamond sheet.
8. The method as described in claim 7, characterized in that, After the diamond sheet is prepared, a hydrogen plasma etching step is also included: hydrogen plasma etching at 800℃ for 0.5h~1h.
9. The method as described in claim 8, characterized in that, The resulting diamond sheet also undergoes mechanical polishing: the surface of the diamond sheet is polished to a roughness Ra < 5 nm.
10. The diamond sheet prepared by the method according to any one of claims 7 to 9, wherein the thermal conductivity of the diamond sheet is above 1500 W / m·K and the bending strength is above 800 MPa.
Citation Information
Patent Citations
Polycrystalline diamond compact and preparation method thereof
CN117020206A
method OF FORMING DIAMOND IMPREGNATED CARBIDE VIA THE IN-SITU CONVERSION OF DISPERSED GRAPHITE
SE9102469D0